Effect of Financing to Deposit Ratio, Net Operating Margin, and Current Ratio on Financial Performance of Sharia Commercial Bank in Indonesia and Malaysia Listed on The Stock Exchange in 2018–2023 - Ridwansyah; Salsabilla Mutia Fortuna; Wiraputra, Jhody W (Mutanaqishah: Journal of Islamic Banking, 2024)
This study aims to examine whether there is an effect of Financing to Deposit Ratio, Net Operating Margin and Curret Ratio on Financial Performance. The population in this study is Sharia commercial banks in Indonesia and Malaysia. The number of samples in this study as many as 30 samples. Sampling technique using purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. Data analysis method using multiple linear regression analysis with Eviews 10. The results of this study provide empirical evidence that partially variable Financing to Deposit Ratio and Net Operating Margin affect Financial Performance. However, the variable Curret Ratio has no effect on Financial Performance. The results of this study give the implication that to improve a financial performance in Islamic commercial banks is Financing to Deposit Ratio and Net Operating Margin.